A Measurement Model of Logistics 5.0 Maturity: An Integrative Review and Framework Proposal Based on Literature - Nazare Toyoda Machado; Carlos Manoel Taboada Rodriguez (ITEGAM-JETIA)
This article explores Logistics 5.0 as an evolution of Industry 4.0, emphasizing the integration of emerging technologies such as artificial intelligence, IoT, and big data in logistics management. It proposes a specific maturity measurement model for Logistics 5.0, structured into five levels: initial, repeatable, defined, managed, and optimized, which evaluate technological readiness, process management, analytical capacity, change management, and sustainability. The analysis highlights gaps in traditional models, proposing dimensions adapted to the demands of digital transformation. The model emphasizes the harmonization between technology, people, and processes, pointing toward more efficient, adaptable, and sustainable logistics. It concludes that the practical application of the model can help companies enhance their competitiveness and sustainability in a dynamic global market.